Hubungan Persepsi dalam Pembelajaran Online dengan Kemandirian Belajar dan Prestasi Belajar Matematika Siswa SMP Negeri 17 Mataram - Riani Permatasari; Sripatmi Sripatmi; Wahidaturrahmi Wahidaturrahmi; Laila Hayati (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This correlation study aims to describe students' perceptions in online learning, learning independence, and student achievement and to determine the relationship between student perceptions in online learning and learning independence and student achievement. The population is all eighth grade students at SMP Negeri 17 Mataram for the 2020/2021 academic year. The sampling technique used purposive sampling technique and the samples obtained were students of class VIIIC. The data collection technique uses a questionnaire on student perceptions in online learning, student learning independence questionnaire, documentation, and interviews. Data analysis technique using Pearson correlation test. The results of data analysis show that: (1) students' perceptions in online learning are mostly in the sufficient category, students' learning independence is mostly in the good category and student achievement is mostly in the bad category; (2) There is a relationship between students' perceptions and learning independence and includes a positive correlation. (3) There is a correlation between students' perceptions of online learning and student achievement, including a negative correlation; (4) there is a correlation between learning independence and student achievement including a negative correlation. For this reason, apart from perceptions, learning independence and learning achievement, it is also a good idea to look at the motivation, talent and interest in student learning.